Lexical Cohesive Devices and English Writing Quality - Khalil, Abdelhamid A.; Abu-Ayyash, Emad A.S (JOURNAL OF ADVANCES IN LINGUISTICS, 2023)
This mixed-methods study investigated the use of lexical cohesive devices (LCD) for 56 Arab English as a Foreign Language (EFL) learners in the UAE. The quantitative descriptive approach was used to find out the frequency of LCD in learners’ essays, and the quantitative correlational approach was implemented to examine the association between LCD and the writing quality. However, the qualitative descriptive approach utilized semi-structured interviews of 4 EFL teachers and 15 EFL learners to identify the challenges that they encountered regarding using LCD in essay writing. The findings demonstrated that repetition and collocations were the most frequently used LCD, while meronyms and hyponyms were the least common in participants’ essays. There was also a moderate positive correlation between cohesive density and the writing quality. The difficulties reported by the participants in dealing with LCD included themes pertaining to awareness and instruction, de-contextualization of cohesive devices (CDs) and feedback and correction.